Monthly incinerator fuel usage of Australian Antarctic Stations - BONNICE, JEREMY (hasPrincipalInvestigator); RATCLIFFE, GUY (processor); SHEERS, ROBERT (processor); Australian Antarctic Data Centre (publisher)
INDICATOR DEFINITION The quantity of fuel used for incinerators at Casey, Davis, Mawson and Macquarie Island stations as measured on a monthly basis and reported in the monthly reports from the Station Plant Inspectors to the Kingston (Head Office) Mechanical Supervisor. TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION The amount of fuel used in Antarctica for waste incineration contributes to environmental impact due to the emissions released. Special Antarctic Blend (SAB), a light diesel like fuel, is used at the stations for the incinerators. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Australian Antarctic stations: Casey (lat 66 deg 16' 54.5& S, long 110 deg 31' 39.4& E), Davis (lat 68 deg 34' 35.8& S, long 77 deg 58' 02.6& E), Mawson (lat 67 deg 36' 09.7& S, long 62 deg 52' 25.7& E) and Macquarie Island (lat 54 deg 37' 59.9& S, long 158 deg 52' 59.9& E). Frequency: Monthly reports Measurement technique: The figures are obtained by direct reading of gauges on the stations on a regular basis. The data are recorded in the Plant Inspectors monthly reports. RESEARCH ISSUES In the future, it is planned to automate the collection of most of this data. LINKS TO OTHER INDICATORS SOE Indicator 47 - Number and nature of incidents resulting in environmental impact SOE Indicator 48 - Station and ship person days SOE Indicator 53 - Recycled and quarantine waste returned to Australia SOE Indicator 54 - Amount of waste incinerated at Australian stations SOE Indicator 56 - Monthly fuel usage of the generator sets and boilers SOE Indicator 58 - Monthly total of fuel used by station vehicles SOE Indicator 60 - Total helicopter hours